A cluster randomized trial on inspiratory effort-targeted pressure support adjustment strategy in patients undergoing assisted mechanical ventilation: protocol for the IT-PSV study - Lu, Wen-Yi; Miao, Ming-Yue; Gao, Ran; Yang, Yan-Lin; Zhang, Linlin; Weng, Li; Zhu, Feng-Xue; Liu, Lei; Zhou, Jian-Xin (Frontiers in Medicine, 2024)
Background: Pressure support ventilation (PSV) is one of the most frequently used ventilator modes in the intensive care unit (ICU). The successful implementation of PSV depends on matching the patient's inspiratory effort with the ventilator support.In clinical practice, the pressure support level is usually set and adjusted according to tidal volume and respiratory rate. However, these parameters may not fully represent the patient's effort. Previous studies have shown that pressure muscle index (PMI), which is measured as the difference between the peak and plateau airway pressure during an end-inspiratory airway occlusion, could reliably determine the low and high inspiratory effort during PSV. Herein we present the study protocol for the Inspiratory effort-Targeted Pressure Support Ventilation (IT-PSV) trial to determine the effect of a PMI-targeted pressure support setting strategy on clinical outcomes in patients undergoing PSV.Methods and Analysis: This is a cluster randomized controlled trial. Sixteen ICUs in academic hospitals will be included, eight of which will be randomly allocated to the PMI-targeted group and eight to the tidal volume/respiratory rate-targeted group.Before the initiation of the study, a four-week comprehensive training program, which includes courses of PSV initiation, pressure support adjustment, and weaning process, will be conducted for all staff in the participating ICUs. Adult patients with acute hypoxic respiratory failure and undergoing PSV within 24 hours will be included.Pressure support setting and adjustment will follow the strategy according to the grouping. The primary outcome is the ventilator-free days at 28 days after enrollment. The patients will be followed up until successful weaning or separation of mechanical ventilation, death, hospital discharge, or until 28 days after randomization, whichever comes first.